Value chain actor perceptions to enhance plastics circularity in Europe—recommendations for future action - zu Castell-Rüdenhausen, Malin; Marttila, Tatu (Frontiers in Sustainability, 2025)
The transition to a circular plastic economy is a priority within the European policy landscape, necessitating enhanced recycling and market uptake for recycled plastics. However, the plastics industry remains governed by linear business models with little focus on circularity, and limited recyclability and markets for recycled plastics often leave incineration and export as the primary methods of waste management. This study examines the current barriers that impede the circularity of plastics in the EU, focusing specifically on non-packaging plastic waste from the automotive, construction, and electronics sectors. We assess value-chain perceptions gathered from a series of semi-structured interviews and workshops conducted within the EU Horizon 2020 NONTOX project, to identify barriers and potential solutions and to produce overarching recommendations for action. These recommendations include enhanced collection and recycling, expansion of recycling capacity, better positioning of new recycling technologies, improved recyclability of products, and support for markets for recycled plastics. The results also highlight the need for high-impact policies to promote a circular plastic economy in the EU. Not only would this support plastics circularity, it would also prevent material loss due to incineration and the export of plastic waste, while contributing to the EU's self-sufficiency in raw materials.